Administration of dicyandiamide to dairy cows via drinking water reduces nitrogen losses from grazed pastures. (December 2014) - Richards, Karl; Fenton, Owen; Watson, Catherine; WELTEN, B. G.; LEDGARD, S. F.; LUO, J.
SUMMARY Oral administration of the nitrification inhibitor dicyandiamide (DCD) to ruminants for excretion in urine represents a targeted mitigation strategy to reduce nitrogen (N) losses from grazed pasture. A farmlet grazing study was undertaken to examine the environmental benefits of administering DCD in trough water to non-lactating Friesian dairy cows that consecutively grazed 12 replicated plots (each 627 m2 with a grazing intensity of up to 319 cows/ha/day) during two grazing rotations in the winter of 2007 in the Waikato region, New Zealand. Nitrate-N (NO3−-N) leaching losses were measured using ceramic cup samplers (600 mm soil depth) and gaseous emissions of nitrous oxide (N2O) were quantified using a static chamber technique in the DCD and control treatments. Administration of DCD in trough water had no effect on daily water intake by dairy cows, which averaged 15 and 18 l/cow/day for the June and August grazing rotations, respectively. This resulted in a mean daily DCD intake of 46 and 110 g/cow/day, respectively. The DCD farmlet had significantly lower NO3−-N concentrations in leachate at the last three samplings, which reduced total NO3−-N leaching losses by 40% (from 32·0 to 19·2 kg N/ha). The DCD treatment reduced N2O emission rates compared to the control treatment following the August grazing, resulting in a 45% reduction in total N2O emissions relative to the control treatment (from 0·49 to 0·27 kg N2O-N/ha). This preliminary study highlights the potential for administering ruminants with DCD as an effective mitigation option for reducing N losses from agricultural systems.